Quiz Quest: An Open-Source Ephemeral Quiz Application For Efficient and Low Cost Interactive Education - Yustus Eko Oktian; Evelin Alim Natadjaja; Evelyn Komalasari Hartono (Center for Research and Community Service, Institut Informatika Indonesia (IKADO) Surabaya, 2025)
The increasing integration of technology in educational settings has highlighted the efficacy of interactive tools, such as online quizzes, in fostering student motivation and engagement. However, the widespread adoption of commercial platforms is often impeded by substantial financial and logistical challenges, including high costs and complex manual setup procedures. To address these limitations, this paper presents Quiz Quest, a novel open-source, ephemeral quiz application. Quiz Quest is engineered using contemporary web service development technologies and features a streamlined, JSON-based question import mechanism, enabling educators to host interactive quizzes on their personal devices. Preliminary assessments indicate that Quiz Quest offers both efficiency and competitive performance. Specifically, compared to established alternatives like Kahoot and Google Forms, Quiz Quest demonstrates a reduction in question setup time of 67-74% during initial use and 71-83% in subsequent uses. Furthermore, it exhibits minimal system resource consumption in low-density classroom environments, with CPU utilization ranging from 0.05% to 0.1% and memory usage stabilizing around 90-95 MB, thereby ensuring compatibility across a variety of hardware configurations. The application also achieved a favorable System Usability Scale score of approximately 75, performing comparably to its counterparts. Consequently, Quiz Quest is posited as an accessible, efficient, and engaging solution for interactive education, offering significant benefits to educators seeking to enhance learning experiences without incurring considerable resource expenditure.